AN ANALYSIS OF FACTORS INFLUENCING MIGRANTS INCOME - Murwanti, Sri; Purnomo, Didit (Universitas Muhammdaiyah Surakarta, 2006)
This study aims to examine the factors influencing the Sukoharjo migrants income in Surakarta. It used multiple linear regressions. In order to find the good estimate, it used classic assumption and statistic tests. The findings of this study indicate that education level and household responsibility has a positive influence on migrants income while working experience has a positive relation to migrants income, but it does not significantly. The findings of classic assumption test indicate that the model used is specific and free from multicolinearity problem while there are heteroskedasticity and morality problems.